Reversibly acetylated lysine residues play important roles in the enzymatic activity of Escherichia coli N‐hydroxyarylamine O‐acetyltransferase. (21st March 2013) - Zhang, Qunfang; Gu, Jing; Gong, Peng; Wang, Xude; Tu, Shun; Bi, Lijun; Yu, Ziniu; Zhang, Zhiping; Cui, Zongqiang; Wei, Hongping; Tao, Shengce; Zhang, Xianen
Abstract : CobB is a bacterial NAD + ‐dependent protein deacetylase. Although progress has been made in functional studies of this protein in recent years, its substrates and biological functions are still largely unclear. Using proteome microarray technology, potential substrates of Escherichia coli CobB were screened and nine proteins were identified, including N ‐hydroxyarylamine O ‐acetyltransferase (NhoA). In vitro acetylation/deacetylation of NhoA was verified by western blotting and mass spectrometry, and two acetylated lysine residues were identified. Site‐specific mutagenesis experiments showed that mutation of each acetylated lysine decreased the acetylation level of NhoA in vitro . Further analysis showed that variant NhoA proteins carrying substitutions at the two acetylated lysine residues are involved in both the O ‐acetyltransferase and N ‐acetyltransferase activity of NhoA. Structural analyses were also performed to explore the effects of the acetylated lysine residues on the activity of NhoA. These results suggest that reversible acetylation may play a role in the activity of Escherichia coli NhoA. Abstract : Potential substrates of Escherichia coli CobB were screened by proteome microarray and nine proteins were identified, including N ‐hydroxyarylamine O ‐acetyltransferase. In vitro acetylation/deacetylation of NhoA was verified and two acetylated lysine residues were identified. Variant NhoA proteins carrying substitutions at the two acetylated lysine residues are involved in both the O ‐acetyltransferase (OAT) activity and the N ‐acetyltransferase (NAT) activity of NhoA.